Effect of social networks intervention in type 2 diabetes: a partial randomised study. Issue 4 (2nd December 2013) - Shaya, Fadia T; Chirikov, Viktor V; Howard, DeLeonardo; Foster, Clyde; Costas, Julian; Snitker, Soren; Frimpter, Jeffrey; Kucharski, Kathrin
Abstract : Background: In this partially randomised intervention study, we assessed the effect of social networks on the improvement of type 2 diabetes management in a largely African–American population in Baltimore. Methods: Patients in the intervention group (n=68) were asked to recruit peers, form small groups, and attend monthly diabetes education sessions, emphasising peer support. Patients in the control group (n=70) were recruited individually to attend standard diabetes education sessions. The primary outcomes were changes in haemoglobin A1C (HbA1c ) and blood glucose. Secondary outcomes included blood pressure, weight, functional status, self-efficacy, perceived cohesion, social network connectedness and diabetes knowledge. General linear mixed models were built to assess mean absolute changes in primary and secondary outcomes at 3 and 6 months. Results: At 6 months from baseline, the social network intervention group achieved a larger reduction in HbA1c of −0.32% (p<0.0001) and blood glucose of −10.6 mg/dL, (p<0.0001) compared to the control group. In analyses of secondary endpoints, the intervention group had more favourable outcomes over time for weight, quality of life, self-efficacy, social network scores and diabetes knowledge, compared to the control group. While blood pressure decreased, and perceived cohesion increased in both groups over the duration of the study, the difference between groups was not statistically significant. Conclusions: The social networks intervention showed improved integration of patients within their existing networks leading to a greater reduction in HbA1c and blood glucose, as well as improved behaviour mediating outcomes.